Belize. Caricom Perspective. No.63/64, p.44. (2011)
Looks at the need for conservation of Belize's coastal zone which includes barrier reefs, mangrove forests, coastal lagoons and estuaries. By protecting the coastal environment, Belize can maintain its tourism and fishing industries.